Theoretical Prediction of Thermoelectric Performance for Layered LaAgOX (X = S, Se) Materials in Consideration of the Four‐Phonon and Multiple Carrier Scattering Processes (Small Methods 3/2023). Issue 3 (13th March 2023) - Bai, Shulin; Zhang, Jingyi; Wu, Mengxiu; Luo, Dongming; Wan, Da; Li, Xiaodong; Tang, Shuwei
Abstract : Thermoelectric Performance In article number 2201368, Tang and co‐workers evaluated the thermoelectric performance of LaAgOX (X = S, Se) materials in consideration of four‐phonon and multiple carrier scattering mechanisms. It is crucial for the rational design of state‐of‐the‐art heteroanionic materials for thermoelectric applications.